2010
DOI: 10.1143/jjap.49.07hf18
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Response of Microbubbles Derived from Phase-Change Nanodroplet

Abstract: An in vitro feasibility test for a novel ultrasound therapy using a type of superheated perfluorocarbon droplet, phase-change nanodroplet (PCND), was performed in gel phantoms with the goal of high selectivity and low invasiveness. Measurements of broadband signal emission revealed that a triggering ultrasound pulse (peak negative pressure of 2.4 MPa) reduces the pressure threshold for cavitation induced by a subsequent ultrasound exposure at an order of magnitude from 2.4 to 0.2 MPa. The maximum allowed inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In response to the limitations inherent in the use of microbubbles and micron-sized droplets, efforts are now focused on nano-sized agents with the development of several techniques to synthesize stable liquid PFC nanodroplets (Kawabata et al, 2010;Rapoport et al, 2010;Zhang and Porter, 2010;Reznik et al, 2011;Sheeran et al, 2011a;Singh et al, 2012). When designed appropriately, PFC nanodroplets can be phase-shifted to gaseous microbubbles by the application of sufficient acoustic energy .…”
Section: Introductionmentioning
confidence: 99%
“…In response to the limitations inherent in the use of microbubbles and micron-sized droplets, efforts are now focused on nano-sized agents with the development of several techniques to synthesize stable liquid PFC nanodroplets (Kawabata et al, 2010;Rapoport et al, 2010;Zhang and Porter, 2010;Reznik et al, 2011;Sheeran et al, 2011a;Singh et al, 2012). When designed appropriately, PFC nanodroplets can be phase-shifted to gaseous microbubbles by the application of sufficient acoustic energy .…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have demonstrated that the time-dependent spectral content of evolving bubbles resulting from vaporized PCCAs may have significantly different spectral information than MCAs [72, 135], which could lead to further contrast-specific imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their highly scattering acoustic properties and nonlinear interactions with incident ultrasound, microbubbles are used in many clinical applications, including assessment of coronary artery disease, hyperlipidaemia, angiogenesis, inflammation and tumour formation. Microbubbles can also be used to assess therapeutic strategies and to facilitate delivery and release of therapeutic agents based on physical interactions of microbubbles with ultrasound [14][15][16] . Furthermore, current research is focused on adapting the microbubbles, through surface modifications, cargo encapsulation or attachment, and other modifications, to allow for additional therapeutic applications [17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%